MANAJEMEN KEPALA MADRASAH DALAM MEMOTIVASI KERJA GURU DI MADRASAH DINIYYAH AL-FUTUHIYYAH ASSALAFIYYAH SUKOREJO SEMPU ANDONG BOYOLALI - Assi, Muhammad Hamid; Ibrahim, Rustam (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
The This study aims to describe and analyze the management of the head of the madrasah in motivating teachers at Madrasah Diniyyah Al-Futuhiyyah Assalafiyyah Sukorejo Sempu Andong Boyolali, as well as to identify the obstacles encountered and the solutions implemented. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The research subjects consisted of the head of the madrasah as the key informant and several permanent and non-permanent teachers selected through purposive sampling. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results revealed that the head of the madrasah implemented four main management functions planning, organizing, actuating, and controlling in an integrated manner to enhance teachers’ work motivation. The head of the madrasah actively served as a leader, mentor, and motivator through spiritual, humanistic, participatory, and exemplary approaches. The main challenges included limited teacher attendance and time, insufficient learning facilities, and the absence of a standardized performance evaluation system. To overcome these issues, the head of the madrasah adopted adaptive strategies such as schedule adjustments, non-material rewards, strengthened communication, and continuous spiritual guidance. This study concludes that religious and humanistic-based leadership effectively fosters a harmonious work atmosphere, enhances teacher motivation and discipline, and sustains the learning process in nonformal Islamic educational institutions. This management model can serve as a reference for other Islamic educational institutions in developing effective, participatory, and value-based management systems that emphasize spiritual development and teacher professionalism. ABSTRAKPenelitian ini bertujuan untuk menganalisis manajemen kepala madrasah dalam memotivasi kerja guru di Madrasah Diniyyah Al-Futuhiyyah Assalafiyyah Sukorejo Sempu Andong Boyolali, serta mengidentifikasi hambatan dan solusi yang diterapkan dalam pelaksanaannya. Pendekatan yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Subjek penelitian meliputi kepala madrasah sebagai informan kunci serta guru tetap dan tidak tetap yang dipilih secara purposive. Analisis data dilakukan menggunakan model Miles dan Huberman, melalui tahap reduksi, penyajian, dan penarikan kesimpulan, serta diuji keabsahannya dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa kepala madrasah menerapkan empat fungsi utama manajemen, yaitu perencanaan, pengorganisasian, pelaksanaan, dan pengawasan, secara terpadu untuk meningkatkan motivasi kerja guru. Kepala madrasah berperan aktif sebagai pemimpin, pembimbing, dan motivator melalui strategi spiritual, humanis, partisipatif, dan keteladanan. Hambatan yang dihadapi meliputi keterbatasan waktu guru, sarana prasarana yang minim, serta belum adanya sistem evaluasi kinerja yang terstandar. Untuk mengatasinya, kepala madrasah menerapkan solusi adaptif berbasis kekeluargaan, pembinaan spiritual, dan penghargaan nonmaterial. Penelitian ini menyimpulkan bahwa kepemimpinan kepala madrasah yang humanis dan religius berperan penting dalam membangun motivasi kerja guru dan menjaga stabilitas lembaga pendidikan nonformal. Model manajemen ini dapat menjadi contoh efektif bagi lembaga pendidikan Islam lainnya dalam mengembangkan sistem manajemen berbasis nilai, partisipatif, dan berorientasi pada pembinaan spiritual serta profesionalitas guru.